Impact of COVID-19 pandemic on the availability of maternal and child health products and childhood vaccines - Tsegaye Melaku; Desta Assefa; Fanta Gashe; Mestawet Getachew; Temesgen Kabeta; Zeleke Mekonnen (Taylor & Francis Group, 2023)
Abstract Background In many low- and middle-income countries, the 2019 novel coronavirus (COVID-19) has challenged efforts to ensure access to and availability of quality maternal, newborn, and child health (MCH) services and essential MCH commodities. Objectives This study evaluated the impact of COVID-19 pandemic on the availability of maternal and child health products and childhood vaccines at selected health facilities in Ethiopia. Methods We have prospectively assessed 28 maternal-child health products and 14 childhood vaccines and accessories, which are listed in the Ethiopian national essential medicines list. Data were collected from 5 hospitals located in the Jimma zone of Oromia regional state in the southwestern part of Ethiopia. We extracted data on drug availability, and order fill rates for these pharmaceutical products between May 2019 and August 2020. Results The overall mean availability of selected maternal and child health products was 43.2%. It was 52.9% (range 21.0-63.6%) prior COVID-19 and 42.6% (range 19-56.4) during COVID-19 time. The average monthly orders fill rates of hospitals for the selected products ranged from 39 to 79%. Before COVID-19 the average order fill rate was near 70% of total orders placed by the hospitals. However, immediately after the COVID-19 case notification in Ethiopia, the percentage of order filled correctly in items and quantities began decreasing. Conclusion This study illustrates that the availability of key essential medicines for maternal and child health in the study area was low. The overall stock-out situation of MCH products has worsened during COVID-19 compared to pre-COVID-19 pandemic. None of the surveyed MCH products met the ideal availability benchmark of 80% in the public hospitals. To allow governments to guarantee these products are constantly available and affordable, a variety of policy frameworks and choices addressing inevitable epidemics should exist.